Deans List for 8 semesters, William Mah Wey Lian receives Royal Education Award Pingat Jaya Cemerlang - Halizan, Mohmood (UMPSA, 2022)
PAYA BESAR, 5 November 2022 - The hard work paid off for William Mah Wey Lian, a graduand of the Bachelor of Chemical Engineering with Honours that he obtained the Dean’s Award for eight semesters with CGPA 3.95 (First Class) and announced as the recipient of the Royal Education Award (Pingat Jaya Cemerlang) in Session 1 of the 17th Universiti Malaysia Pahang (UMP) Convocation Ceremony recently.